Synthesis, characterization and thermal degradation of poly[2-(3-p-bromophenyl-3-methylcyclobutyl)-2-hydroxyethylmethacrylata] - Demirelli, Kadir; Coşkun, Mehmet (John Wiley and Sons Ltd, 1999)
In this work, 2-(3-p-bromophenyl-3-methylcyclobutyl)-2-hydroxyethylmethacrylate (BPHEMA) [monomer] was synthesized by the addition of methacrylic acid to 1-epoxyethyl-3-bromophenyl-3-methyl cyclobutane. The monomer and poly(BPHEMA) were characterized by FT-IR and [1H] and [13C]NMR. Average molecular weight, glass transition temperature, solubility parameter, and density of the polymer were also determined. Thermal degradation of poly[BPHEMA] was studied by thermogravimetry (TG), FT-IR. Programmed heating was carried out at 10°Cmin-1 from room temperature to 500°C. The partially degraded polymer was examined by FT-IR spectroscopy. The degradation products were identified by using FT-IR, [1H] and [13C]NMR and GC-MS techniques. Depolymerization is the main reaction in thermal degradation of the polymer up to about 300°C. Percentage of the monomer in CRF (Cold Ring Fraction) was estimated at 33% hi the peak area of the GC curve. Intramolecular cyclization and cyclic anhydride type structures were observed at temperatures above 300°C. The liquid products of the degradation, formation of anhydride ring structures and mechanism of degradation are discussed. © 1999 Society of Chemical Industry.
Keywords: 2-hydroxyethylmethacrylate; Synthesis; Thermal degradation